The Ophthalmological Manifestations of Various Inborn Errors of Metabolism: A Narrative Review - Abdolreza Medghalchi; Afagh Hassanzadeh Rad; Setila Dalili (Mazandaran University of Medical Sciences, 2021)
Context: Inborn errors of metabolism or Inherited Metabolic Disorders (IMD) are a class of genetic disorders that occur because of single-gene defects. Evidence Acquisition: In this narrative review article, the authors searched Institute for Scientific Information (ISI), Web of Science, PubMed, and Google Scholar for the relevant evidence. Results: The ocular manifestations of IMDs can be distinguished in different diseases such as Albinism, Cystinosis, Homocystinuria, and Sulfite oxidize deficiency, Mannosidosis, Fucosidosis, Sialidosis, etc. Conclusions: Due to the direct toxic mechanisms of abnormal metabolites on eyes and regarding the effect of eye monitoring on the follow-up, management, and treatment, a detailed ophthalmological assessment is essential.